2020
DOI: 10.2147/jbm.s232655
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Review on the Impact of Body Mass Index on Outcomes in Pediatric Leukemia</p>

Abstract: In the last decades, adults and pediatric obesity have become a major issue in developed countries. Considerable research has been conducted in patients with acute lymphoblastic (ALL) and myeloid leukemia (AML) with the aim of correlating body mass index (BMI) and outcomes in patients undergoing chemotherapy for hematological diseases. In adults, a high BMI has been associated with increased leukemia-related mortality. Whether a similar effect exists in the pediatric setting remains controversial. Some of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Therefore, nutritional treatment should become an integral component of medical care for pediatric patients with malignancies undergoing anticancer treatment. Proper nutrition is associated with better treatment outcomes, responses, and tolerance of chemotherapy, helps to alleviate side effects of treatment, improves the quality of life, and significantly impacts patients' physical, motor, cognitive, and neurologic development [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, nutritional treatment should become an integral component of medical care for pediatric patients with malignancies undergoing anticancer treatment. Proper nutrition is associated with better treatment outcomes, responses, and tolerance of chemotherapy, helps to alleviate side effects of treatment, improves the quality of life, and significantly impacts patients' physical, motor, cognitive, and neurologic development [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional status of children with malignancies is of crucial significance in terms of short-term consequences, such as tolerance of chemotherapy, response to chemotherapy and radiotherapy, drug metabolism, rate of treatment-related complications, and mortality and quality of life, as well as the long-term consequences-survivors' growth, motor, cognitive, and neurologic development, body composition, bone maturation, and mineral density [1][2][3][4][5][6][7]. With an understanding of this, nutritional support should be an integral component of complex anticancer management.…”
Section: Introductionmentioning
confidence: 99%
“…39 Nutritional Assessment: Furthermore, a link between obesity and higher rates of fatal infection and more treatment-related mortality has been suggested. 44,45…”
Section: Obese Patientsmentioning
confidence: 99%
“…Similar considerations were reported by Triarico et al, 46 who concluded that a personalized evaluation of nutritional risk at diagnosis and close monitoring of nutritional status are crucial for ensuring a timely and personalized nutritional intervention, which may potentially improve tolerance to chemotherapy and survival, in turn preventing prolonged hospitalization for infections. In a recent review, Paviglianiti 45 underscored how being at either extreme of the index (underweight or obese) is associated with worse outcomes and toxicities in children with leukemia or undergoing hematopoietic stem-cell transplantation (HSCT).…”
Section: Cancer Outcomes In Children With Malnutrition In High Income...mentioning
confidence: 99%
“…Existen estudios que abordan el impacto de la obesidad en los resultados de pacientes pediátricos con LLA, sin embargo en población adulta son escasos 29 . Por lo que comprender el impacto pronóstico del IMC no solo tendría implicaciones clínicas en los pacientes con LLA, sino también en la de salud pública con intervención preventiva que podría mejorar sus resultados 42 . Asimismo, determinar la relación entre el estado nutricional y LLA podría generar mejoras significativas en la supervivencia de dichos pacientes 43 .…”
Section: Estado Nutricional Y Supervivencia En Pacientes Con Llaunclassified